PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUALTERHADAP KINERJA PERAWAT RUMAH SAKIT HARAPAN BUNDA - CITRA, YOLANDA UTAMA; Simanjuntak, Jontro (SCIENTIA JOURNAL, 2021)
ABSTRACT This study aims for determine the effect of intellectual intelligence, emotional intelligence and spiritual intelligence on the performance of nurses at Harapan Bunda Hospital. Nurses who work at Arapan Bunda Hospital, the population and sample in this study were 116 people, using quantitative research methods and analysis, namely descriptive analysis, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient analysis determination (R²), t test and F test using the SPSS version 25 program. Determination (R²) shows that the variables of this study are 50% of the nurse's performance. The results of multiple linear regression test showed that intellectual intelligence had an effect of 23.5%, emotional intelligence had an effect of 28.3% and spiritual intelligence had an effect of 21.9% on nurse performance. The t-test has the results of research on intellectual intelligence, emotional intelligence and spiritual intelligence have a significant and positive effect on the performance of nurses at Harapan Bunda Hospital. While the F test Intellectual intelligence, emotional intelligence and spiritual intelligence on the performance of nurses jointly affect the performance of nurses at Harapan Hospital. So, Harapan Bunda Hospital should evaluate the variables in this study to improve the work of Harapan Bunda Hospital nurses. Keywords: Intellectual Intelligence; Emotional Intelligence; Spiritual Intelligence